Renal Masses Detected on FDG PET/CT in Patients With Lymphoma: Imaging Features Differentiating Primary Renal Cell Carcinomas From Renal Lymphomatous Involvement - Nicolau, Carlos (AJR Am J Roentgenol, 2017)
OBJECTIVE: The purpose of this study is to analyze the (18)F-FDG PET/CT features of solid renal masses detected in patients with lymphoma and to evaluate the ability of PET/CT to differentiate renal cell carcinoma (RCC) from renal lymphomatous involvement. MATERIALS AND METHODS: Thirty-six patients with solid renal masses on PET/CT performed for staging or follow-up of lymphoma were evaluated retrospectively. The features recorded for each renal mass included the following standardized uptake values (SUVs) on PET/CT: the maximum SUV (SUV(max)), the mean SUV (SUV(mean)), the ratio of the SUV(max) of the tumor to that of the normal kidney cortex, the ratio of the SUV(mean) of the tumor to that of the normal kidney cortex, the ratio of the SUV(max) of the tumor to that of the normal liver, and the ratio of the SUV(mean) of the tumor to that of the normal liver. Renal mass size and margins (well defined vs infiltrative) and the presence of calcifications were evaluated on CT. Renal biopsy results were used as the reference standard. Relationships between imaging parameters and histopathologic findings were assessed. RESULTS: Of the 36 renal masses evaluated, 22 (61.1%) were RCCs and 14 (38.9%) were renal lymphomas. All SUV metrics were higher for renal lymphomas than for RCCs (p< 0.0001, for all). All renal lymphomas had an SUV(max) higher than 5.98 g/mL (median, 10.99 g/mL), whereas all RCCs had an SUV(max) lower than 5.26 g/mL (median, 2.91 g/mL). No statistically significant differences in mass size or margins were found between RCCs and renal lymphoma. CONCLUSION: PET/CT features may be useful for differentiating RCCs from renal involvement in patients with lymphoma with solid renal masses.